The AI-Driven Transformation in New Materials Manufacturing and the Development of Intelligent Sports - Fang Wang; Shunnan Jiang; Jun Li (Applied Sciences)
The advancement of materials science has had a profound, even revolutionary, impact on sports. Materials are used in the sports field, equipment, and sportswear, each with distinct functionality and safety requirements. Additionally, diverse sport-related data require physical devices for collection, analysis, and storage, which can be crucial in athlete selection, performance assessment, strategy planning, and training optimization. Artificial intelligence, with its strong cognitive abilities, learning capacity, large-scale data processing, and adaptability, can effectively enhance efficiency, reduce errors, and lower costs. The integration of advanced materials and artificial intelligence (AI) has significantly enhanced the efficiency and precision of research and development in sports-related technologies, while also facilitating the innovation of training methodologies through intelligent data analytics. This convergence has initiated a transformative phase in the digitalization of the sports industry. Anchored in both theoretical analysis and practical implementation, this study seeks to construct a systematic cognitive framework that elucidates the interrelationship between material science and AI technologies. The aim is to assist sports professionals in understanding and leveraging this technological shift to support strategic decision-making and to foster sustainable, high-quality development within the field.